Polymorphisms of 20 regulatory proteins between Mycobacterium tuberculosis and Mycobacterium bovis - Bigi, María Mercedes; Blanco, Federico Carlos; Araujo, Flabio Ribeiro de; Thacker, Tyler C.; Zumarraga, Martin Jose; Cataldi, Angel Adrian; Soria, Marcelo Abel; Bigi, Fabiana (2017)
Mycobacterium tuberculosis and Mycobacterium bovis are responsible for tuberculosis in humans and animals, respectively. Both species are closely related and belong to the Mycobacterium tuberculosis complex (MTC). M. tuberculosis is the most ancient species from which M. bovis and other members of the MTC evolved. The genome of M. bovis is over >99.95% identical to that of M. tuberculosis but with seven deletions ranging in size from 1 to 12.7 kb. In addition, 1200 single nucleotide mutations in coding regions distinguish M. bovis from M. tuberculosis. In the present study, we assessed 75 M. tuberculosis genomes and 23 M. bovis genomes to identify non-synonymous mutations in 202 coding sequences of regulatory genes between both species. We identified species-specific variants in 20 regulatory proteins and confirmed differential expression of hypoxia-related genes between M. bovis and M. tuberculosis